Ответ:
1) (2/7 + 3 1/2) x 4 2/3 = (2/7 + 7/2)x4 2/3 = 1 x 4 2/3= 4 2/3
2) (4 1/5 - 2 3/4) x 2 2/19 = (20/5 - 11/4) x 2 2/19 = (80/20 - 55/20) x 2 2/19 = 25/20 x 40/19 = 25/1 x 2/19 = 50/19 = 2 12/19
позже сделаю больше
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1) (2/7 + 3 1/2) x 4 2/3 = (2/7 + 7/2)x4 2/3 = 1 x 4 2/3= 4 2/3
2) (4 1/5 - 2 3/4) x 2 2/19 = (20/5 - 11/4) x 2 2/19 = (80/20 - 55/20) x 2 2/19 = 25/20 x 40/19 = 25/1 x 2/19 = 50/19 = 2 12/19
позже сделаю больше